Pyoverdine synthesis by the Mn(II)-oxidizing bacterium Pseudomonas putida GB-1 - Parker, Dorothy L.; Lee, Sung-Woo; Geszvain, Kati; Davis, Richard E.; Gruffaz, Christelle; Meyer, Jean-Marie; Torpey, Justin W.; Tebo, Bradley M. (Frontiers in Microbiology, 2014)
When iron-starved, the Mn(II)-oxidizing bacteria Pseudomonas putida strains GB-1 and MnB1 produce pyoverdines (PVDGB-1 and PVDMnB1), siderophores that both influence iron uptake and inhibit manganese(II) oxidation by these strains. To explore the properties and genetics of a PVD that can affect manganese oxidation, LC-MS/MS and various siderotyping techniques were used to identify the peptides of PVDGB-1 and PVDMnB1 as being (for both PVDs): chromophore-Asp-Lys-OHAsp-Ser-Gly-aThr-Lys-cOHOrn, resembling a structure previously reported for P. putida CFML 90-51, which does not oxidize Mn. All three strains also produced an azotobactin and a sulfonated PVD, each with the peptide sequence above, but with unknown regulatory or metabolic effects. Bioinformatic analysis of the sequenced genome of P. putida GB-1 suggested that a particular non-ribosomal peptide synthetase, coded by the operon PputGB1_4083-4086, could produce the peptide backbone of PVDGB-1. To verify this prediction, plasmid integration disruption of PputGB1_4083 was performed and the resulting mutant failed to produce detectable PVD. In silico analysis of the modules in PputGB1_4083-4086 predicted a peptide sequence of Asp-Lys-Asp-Ser-Ala-Thr-Lsy-Orn, which closely matches the peptide determined by MS/MS. To extend these studies to other organisms, various Mn(II)-oxidizing and non-oxidizing isolates of P. putida, P. fluorescens, P. marincola, P. fluorescens-syringae group, P. mendocina-resinovorans group and P. stutzerii group were screened for PVD synthesis. The PVD producers (12 out of 16 tested strains) were siderotyped and placed into four sets of differing PVD structures, some corresponding to previously characterized PVDs and some to novel PVDs. These results combined with previous studies suggested that the presence of OHAsp or the flexibility of the pyoverdine polypeptide may enable efficient binding of Mn(III).